The iPad pocket guide - Carlson, Jeff (Peachpit Press, 2012)
Inexpensive and to-the-point, The iPad Pocket Guide is a complete companion to all the features and functions of the iPad including: Facetime, HD Video, Mail, Safari, Photos and Video, App Store, iBooks, Maps, Notes, Calendar, Contacts, and more. It will help you get up-and-running with easy to understand instructions and then show you hidden gems and tips to make you a true iPad expert.